(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Molluscs comprises a diverse array of invertebrate animals found in marine, freshwater, and terrestrial environments worldwide. With over 100,000 described species, mollusks exhibit remarkable morphological diversity, ranging from tiny snails to giant squids. The ecological importance of mollusks cannot be overstated. They play vital roles in ecosystems as herbivores, carnivores, scavengers, and filter feeders, contributing to nutrient cycling and serving as food sources for numerous organisms. Some molluscs, such as oysters and mussels, have significant economic value in aquaculture and fisheries. This study explores the nutritional composition of two common edible mollusk species, Perna viridis (green mussel) and Marcia recens (yellow foot clam), harvested from the estuarine waters along the southwest coast of India. The investigation focused on determining the protein, carbohydrate, cholesterol, triglyceride, and vitamin C content of these mollusks, providing insights into their potential as seafood sources. Further studies are needed to assess additional health markers and nutritional indices to fully understand the suitability of these mollusks as dietary sources. Overall, this study underscores the nutritional value and potential health implications of consuming P. viridis and M. recens, highlighting the importance of continued research in this area for fisheries and aquaculture management. Additionally, mollusks are utilized in medical research and environmental monitoring, further highlighting their importance beyond ecological roles. Understanding the diversity and ecological significance of Phylum Mollusca is essential for conservation efforts and the sustainable management of ecosystems